The effect of organizational ethics on increasing the performance of workers in small and medium-sized enterprises - Sejfijaj, Osman; Sabedini, Hekuran; Tahiri, Alberta; Kovaci, Idriz (Nurture, 2024)
Purpose: This study investigates the relationship between organizational ethics and job performance in small and medium-sized enterprises (SMEs), aiming to uncover how organizational ethics impacts employee performance. Design/Methodology/Approach: Employing various statistical analyses, the study explores the correlation between organizational ethics and job performance, utilizing a robust methodology to ascertain the influence of ethical practices on employee productivity. Findings: The study reveals a distinct negative correlation between organizational ethics and job performance in SMEs, indicating that higher organizational ethics levels are associated with lower employee job performance. Linear regression analysis confirms this negative influence, highlighting the significance of ethical considerations in shaping job performance outcomes. Conclusion: Despite the significant impact of organizational ethics on job performance, no significant gender differences in organizational ethics or job performance levels were identified in SMEs. Research Limitations/Implications: Acknowledging limitations such as sample size variations and industry-specific factors, the study proposes avenues for future research to delve deeper into these aspects and enhance the applicability of the findings. Practical Implications: The findings emphasize the importance of promoting ethical behavior in SMEs to enhance overall job performance and productivity, highlighting the need for heightened awareness of organizational ethics in managerial practices. Contribution to Literature: This study contributes a new perspective to the understanding of organizational ethics and job performance in SMEs, offering insights for management practices and contributing to the literature on organizational ethics in small business contexts.